Virome Sequencing of the Human Intestinal Mucosal–Luminal Interface - Yan, Austin; Butcher, James; Mack, David; Stintzi, Alain (Frontiers in Cellular and Infection Microbiology, 2020)
While the human gut virome has been increasingly explored in recent years, nearly all studies have been limited to fecal sampling. The mucosal–luminal interface has been established as a viable sample type for profiling the microbial biogeography of the gastrointestinal tract. We have developed a protocol to extract nucleic acids from viruses at the mucosal–luminal interface of the proximal and distal colon. Colonic viromes from pediatric patients with Crohn's disease demonstrated high interpatient diversity and low but significant intrapatient variation between sites. Whole metagenomics was also performed to explore virome–bacteriome interactions and to compare the viral communities observed in virome and whole metagenomic sequencing. A site-specific study of the human gut virome is a necessary step to advance our understanding of virome–bacteriome–host interactions in human diseases.